2023
DOI: 10.3171/2022.6.jns2274
|View full text |Cite
|
Sign up to set email alerts
|

Use of heparin to rescue immunosuppressive monocyte reprogramming by glioblastoma-derived extracellular vesicles

Abstract: OBJECTIVE The profound immunosuppression found in glioblastoma (GBM) patients is a critical barrier to effective immunotherapy. Multiple mechanisms of tumor-mediated immune suppression exist, and the induction of immunosuppressive monocytes such as myeloid-derived suppressor cells (MDSCs) is increasingly appreciated as a key part of this pathology. GBM-derived extracellular vesicles (EVs) can induce the formation of MDSCs. The authors sought to identify the molecular consequences of these interactions in myelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…HSPGs are abundantly present in the brain endothelium [5557] and are known to be involved in the receptor-mediated endocytosis of HIV-1 particles [57, 58] and HIV-TAT protein [59]. Many reports have demonstrated that EVs from cancer cells [6062] interact with HSPGs and the role of the HSPG inhibition on the effects of EV-HSPG interactions. Atai et al demonstrated involvement of HSPG receptors in the attachment and internalization of EVs derived from U87/GBM 11/5 and 293T/HUVEC into the respective recipient cells [21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HSPGs are abundantly present in the brain endothelium [5557] and are known to be involved in the receptor-mediated endocytosis of HIV-1 particles [57, 58] and HIV-TAT protein [59]. Many reports have demonstrated that EVs from cancer cells [6062] interact with HSPGs and the role of the HSPG inhibition on the effects of EV-HSPG interactions. Atai et al demonstrated involvement of HSPG receptors in the attachment and internalization of EVs derived from U87/GBM 11/5 and 293T/HUVEC into the respective recipient cells [21].…”
Section: Resultsmentioning
confidence: 99%
“…HSPGs are abundantly present in the brain endothelium [53][54][55] and are known to be involved in the receptor-mediated endocytosis of HIV-1 particles [55,56] and HIV-TAT protein [57]. Many reports have demonstrated that EVs from cancer cells [58][59][60] Assuming that heparin blockade of HSPG receptors in recipient cells would inhibit dynamindependent endocytosis [53] and macropinocytosis [61] pathways, our goal was to determine if HSPG blockade may have an effect on the uptake of EVs into the recipient BECs. The internalization/adherence of EVs have been observed as early as 30-minutes post EV exposure to the recipient cells [62,63].…”
Section: Effect Of Heparin On Ev Uptakementioning
confidence: 99%
“…In GBM, the secretion of EVs involves a unique mechanism in which these vesicles interact with heparan sulfate proteoglycans (HSPGs) and MDSCs, inducing the transformation of MDSCs [441]. This process can be inhibited by heparin, leading to a reduction in the number of MDSCs in GBM [449]. EVs derived from GBM cells can reprogram normal MONs, promoting their differentiation into MDSCs and subsequent suppression of T cell function [449].…”
Section: Immunosuppressive Effect Of Mdsc In Glioblastoma the Signali...mentioning
confidence: 99%
“…This process can be inhibited by heparin, leading to a reduction in the number of MDSCs in GBM [449]. EVs derived from GBM cells can reprogram normal MONs, promoting their differentiation into MDSCs and subsequent suppression of T cell function [449]. Again, heparin can inhibit this reprogramming process and restore T cell function.…”
Section: Immunosuppressive Effect Of Mdsc In Glioblastoma the Signali...mentioning
confidence: 99%
“…Another mechanism of heparin action is that heparin causes aggregation of vesicles ( Atai et al, 2013 ). Finally, heparin treatment helped to avoid monocyte reprogramming during incubation with patient-derived glioblastoma vesicles ( Himes et al, 2022 ). Unfortunately, studies on heparin in glioblastoma model in vivo were not found in literature.…”
Section: Future Perspectives Of Ev-based Gbm Treatmentmentioning
confidence: 99%